2011
DOI: 10.5665/sleep.1280
|View full text |Cite
|
Sign up to set email alerts
|

Narcolepsy with Cataplexy Associated with Nocturnal Compulsive Behaviors: A Case-Control Study

Abstract: INTRODUCTIONNarcolepsy with cataplexy (NC) is a central nervous system hypersomnia, characterized by excessive daytime sleepiness (EDS), cataplexy (transient loss of muscle tone triggered by emotions), sleep paralysis, hypnagogic hallucinations, and disrupted nocturnal sleep. 1 It is caused by the selective loss of hypothalamic neurons 2 producing hypocretin-1 and 2 (or orexin-A and B), 3,4 two related peptides involved in regulation of sleep-wake transition, energy homeostasis, feeding behavior, and reward sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 50 publications
2
22
1
1
Order By: Relevance
“…We assume that smoking habits are similar in Slovakia. The proportion of smokers in our NC population is about 50% higher than in an Italian study where, however, was the same percentage of smokers in the control group as is reported for the Czech population, so also the Italian study has shown higher frequency of smoking among patients with NC, the authors explain this higher rate with the stimulatory action of nicotine (Palaia et al, 2011). Higher proportion of current smokers in NC than in controls (37.2% vs. 21.7%) was also reported in recent large French study (Barateau et al, 2016).…”
Section: Discussioncontrasting
confidence: 37%
“…We assume that smoking habits are similar in Slovakia. The proportion of smokers in our NC population is about 50% higher than in an Italian study where, however, was the same percentage of smokers in the control group as is reported for the Czech population, so also the Italian study has shown higher frequency of smoking among patients with NC, the authors explain this higher rate with the stimulatory action of nicotine (Palaia et al, 2011). Higher proportion of current smokers in NC than in controls (37.2% vs. 21.7%) was also reported in recent large French study (Barateau et al, 2016).…”
Section: Discussioncontrasting
confidence: 37%
“…[16][17][18][19][20][21] In fact, even among SRED cases where RLS frequency was not addressed, there is a peculiar incidence of conditions frequently comorbid with RLS, such as Parkinson disease 22 and narcolepsy. 23 Like nondysfunctional nocturnal eating (a non-pathological variation of SRED), RLS may be mild or only minimally interfering with sleep onset. Further, RLS sensations are often difficult for patients to define, and current symptomatic criteria are not easily translated between languages.…”
Section: Epidemiology Of Ne/sred and Rlsmentioning
confidence: 99%
“…Although the obesity has been clearly linked to low cerebrospinal fluid (CSF) HCRT1 levels (Heier et al, 2011; Nishino et al, 2001; Poli et al, 2009) and abdominal fat deposits (Kok et al, 2003; Poli et al, 2009), the cause of the BMI increase in narcolepsy has been challenging to parse. Binge eating, irresistible food cravings, and sleep-related eating disorder have been reported in approximately a quarter of narcoleptic patients (Fortuyn et al, 2008; Palaia et al, 2011), but this population also has reduced daily caloric intake compared to healthy controls (Chabas et al, 2007; Lammers et al, 1996). Like other overweight people, patients with narcolepsy who are obese tend to have lower resting metabolic rates (Chabas et al, 2007).…”
Section: Overview Of Narcolepsymentioning
confidence: 99%